Hubungan Pengetahuan Gizi Ibu Hamil terhadap Peningkatan Berat Badan Selama Kehamilan di Puskesmas Bandar Lampung - Tasya Khalis Ilmiani; Dian Isti Angraini; Rizki Hanriko (MAJORITY, 2020)
Adequacy of nutrition for pregnant women is very important because it can contribute to both the mother and the baby. Pregnant women with poor nutritional status can cause a risk of fetal development, disability in infants, low birth weight, and death before birth. Nutrition in pregnant women is influenced by the mother's nutritional knowledge during pregnancy. This study aims to determine the relationship between nutritional knowledge in pregnant women and weight gain during pregnancy. The design of study was cross sectional analytic using primary data obtained from the questionnaires and secondary data obtained from the KIA / KMS book that include maternal weight. Sampling was examined at Puskesmas Bandar Lampung which is Kedaton, Way Kandis, Satellite, Sukaraja, Sukabumi, and Simpur Puskesmas in 2018. The total sample is 130 pregnant womans with purposive sampling technique. The data analysis using Chi Square with α = 0.05 and CI = 95%. The results of the research showed that there is a relationship between nutritional knowledge in pregnant women and weight gain during pregnancy in Bandar Lampung Primary Health Center with a value of p = 0.003. From the results of this study it can be concluded that nutritional knowledge in pregnant women influences the weight gain during pregnancy.